2017
DOI: 10.5603/kp.a2016.0137
|View full text |Cite
|
Sign up to set email alerts
|

Platelet distribution width predicts left ventricular dysfunction in patients with acute coronary syndromes treated with percutaneous coronary intervention

Abstract: A b s t r a c t Background:The role of platelets in the pathophysiology of acute coronary syndromes (ACS) is undeniable, but precise relationships between platelet activity and treatment outcomes are a matter of continuant investigation. Among platelet indices, mean platelet volume (MPV) has proven to be a valuable predicting factor in cardiac patients. However, platelet distribution width (PDW) is reported to be a more specific marker of platelet reactivity. Thus, application of PDW in risk stratification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
2
11
0
1
Order By: Relevance
“…In our study, no correlation was found between PDW and the severity and extent of coronary artery disease and similar results were observed in a prospective study performed by Luca et al [ 53 ]. PDW correlates with the occurrence of heart failure in patients with ACS after PCI in the study of Kowara et al [ 54 ] and also our study PDW was found to be a predictor for in-hospital heart failure development in ACS patients.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, no correlation was found between PDW and the severity and extent of coronary artery disease and similar results were observed in a prospective study performed by Luca et al [ 53 ]. PDW correlates with the occurrence of heart failure in patients with ACS after PCI in the study of Kowara et al [ 54 ] and also our study PDW was found to be a predictor for in-hospital heart failure development in ACS patients.…”
Section: Discussionsupporting
confidence: 84%
“…Also, other authors analysed the PDW as a marker in patients with acute myocardial infarction . Similarly, to our study, the PDW value above 16 fL was the risk factor of the unfavourable outcome.…”
Section: Discussionsupporting
confidence: 83%
“…PDW measured on admission is a cheap and generally available biomarker which allows for predicting the development of heart failure in patients with ACS after PCI [ 60 ]. Bekler et al showed that an increased level of PDW (>17%) was related to the severity of CAD in patients with ACS.…”
Section: Platelet Distribution Width (Pdw)mentioning
confidence: 99%